Chapter Dalla Vita nova al Paradiso: alcune riflessioni sul percorso poetico-traduttorio di Ol'ga Sedakova - KARAFILLIDIS, IRIS (Biblioteca di Studi di Filologia Moderna, 2022)
In the complex panorama of Russian translations of Dante, Ol'ga Sedakova occupies a particularly important place, representing the figure of an intellectual who not only devoted long studies to Dante's poetics and language as well as attempted translation, but who also introjected the themes and scope of his cultural heritage into her own work. In this essay, Sedakova's poetic and translating career is analysed by showing how, from her first publications in the samizdat journals of the 1970s to her most recent publications in 2020, the figure of Dante, his work and themes have always been given central importance.